Study on mechanical performance and temperature profile characteristic of polyethylene terephthalate modified asphalt - Amanina Farhana, Ahmad (2024)
Malaysian cities such have been reported to experience a temperature rise of 0.6 ̊C in a decade. In Malaysia, asphalt pavements have the ability to absorb a higher heat flux, resulting in the production of an average of 400 to 600 MJ/m2 of solar radiation per month due to the country's equatorial geographical profile, thereby increasing pavement temperatures. Pavements subjected to such elevated temperatures are susceptible to experiencing rutting. Therefore, a study on the temperature profile of the asphalt pavement layer would be useful in the development of pavement energy harvesting in Malaysia. This study investigated the impact of using polyethylene terephthalate (PET) as an aggregate coating to enhance pavement mixture and its influence on temperature profiles within the pavement. Temperature profiles were collected using thermocouples at each layer of pavement samples over 6-hour periods under a simulated temperature range of 30°C to 70°C, based on actual temperatures recorded for the East Coast of Malaysia. The temperatures were initially recorded at 30°C and then increased by 5°C every 6 hours until reaching a temperature of 70°C. Employing a dry process, the research aimed to determine the optimal percentage of PET content for aggregate coating and its effects on bituminous mixture properties when compared to a conventional mixture. PET was introduced in powdered form, with particle sizes range 0.425mm to 0.075mm, and the Marshall mix design method (ASTM D6927) was utilized. Initially, 15 samples were employed to ascertain the optimal bitumen content (OBC), which was found to be 4.7% by weight of the bituminous mixture. Various PET content at 2%, 4%, 6%, 8%, and 10% by weight of the 4.7% OBC were then tested to determine the optimal modifier content (OMC). The results indicated that the OMC for PET was 6.3%, as it exhibited favorable stability at 23.5 kN, a bulk density of 2.338 g/cm³, 74% bitumen voids filled (VFB), a flow of 3.4 mm, air voids (AV) at 3.8%, and voids in the mineral aggregate (VMA) at 14.4%. The 6.3% PET mixture also demonstrated a 7.1% increase in stability compared to the conventional mixture. Regarding temperature profiles, it was observed that the surface temperature of the modified pavement sample was 2.1°C higher than that of the unmodified asphalt sample. Furthermore, the bottom layer temperature was 3.3°C higher in the modified sample compared to the unmodified sample. The maximum subgrade surface temperature for the modified pavement sample reached nearly 65.9°C, whereas the maximum subgrade temperature at a depth of 35 cm was 28.3°C. In conclusion, PET was proven to be a suitable material for enhancing pavement strength when added in the right proportion as an aggregate coating and also can increase the potential of energy harvesting by study the temperature profile of pavement.